Physics - Keller, Frederick J.; Gettys, Edward W.; Skove, Malcolm J. (United States of America. McGraw-Hill , Inc.)
"The book is designed for a sequence of courses in physics for science and engineering majors. This sequence usually incorporates two or three. The text is available in two versions: Physics, which contains 39 chapters and ends with the Bohr model of hydrogen; and Physics: Classical and Modern, which contains an additional six chapters on modern. We presume that students beginning in this physics sequence will be concurrently enrolled in a first course in calculus."
Includes appendix and index.
English text.
Keywords: Physics